What does Medicaid expansion mean for cancer screening and prevention? Results from a randomized trial on the impacts of acquiring Medicaid coverage. Issue 5 (9th December 2015) - Wright, Bill J.; Conlin, Alison K.; Allen, Heidi L.; Tsui, Jennifer; Carlson, Matthew J.; Li, Hsin Fang
Abstract : BACKGROUND: The Oregon Medicaid lottery provided a unique opportunity to assess the causal impacts of health insurance on cancer screening rates within the framework of a randomized controlled trial. Prior studies regarding the impacts of health insurance have almost always been limited to observational evidence, which cannot be used to make causal inferences. METHODS: The authors prospectively followed a representative panel of 16, 204 individuals from the Oregon Medicaid lottery reservation list, collecting data before and after the Medicaid lottery drawings. The study panel was divided into 2 groups: a treatment group of individuals who were selected in the Medicaid lottery (6254 individuals) and a control group who were not (9950 individuals). The authors also created an elevated risk subpanel based on family cancer histories. One year after the lottery drawings, differences in cancer screening rates, preventive behaviors, and health status were compared between the study groups. RESULTS: Medicaid coverage resulted in significantly higher rates of several common cancer screenings, especially among women, as well as better primary care connections and self‐reported health outcomes. There was little evidence found that acquiring Medicaid increased the adoption of preventive health behaviors that might reduce cancer risk. CONCLUSIONS: Medicaid coverage did not appear to directly impact lifestyle choices that might reduce cancer risk, but it did provide access to important care and screenings that could help to detect cancers earlier. These findings could have long‐term population health implications for states considering or pursuing Medicaid expansion. Cancer 2016;122:791–797. © 2015 American Cancer Society . Abstract : Access to Medicaid appears to significantly increase the use of certain preventive screenings in a low‐income population, especially among those with an elevated family risk of cancer. Health insurance expansion might be an important strategy for addressing cancer disparities by ensuring earlier detection in underserved or at‐risk populations..